Therapists’ Experiences With the Effectiveness and Feasibility of Videoconference-Based Eye Movement Desensitization and Reprocessing - Mischler, Corinna; Hofmann, Arne; Behnke, Alexander; Matits, Lynn; Lehnung, Maria; Varadarajan, Suchithra; Rojas, Roberto; Kolassa, Iris-Tatjana; Tumani, Visal (Frontiers in Psychology, 2021)
Research on the effectiveness and applicability of Eye Movement Desensitization and Reprocessing (EMDR) via videoconference is sparse. Considering the emerging use of internet-based psychotherapy during the COVID-19 pandemic, information on videoconference-based EMDR (eEMDR) would be beneficial for many therapists. In this study 23 therapists from the EMDR-Institute in Germany provided information about their experiences with eEMDR within a questionnaire-based survey. Information on the effectiveness and the course of 102 eEMDR sessions was recorded. Results showed the potential of eEMDR as an effective and viable method. The decrease in the subjective unit of disturbance (SUD), which is an important indicator of treatment outcome, found to be at similar level compared to previous EMDR studies that were not administered in eEMDR format. The most important predictor of the SUD decrease was the type of bilateral stimulation used within the eEMDR sessions. Eye movements resulted in significantly greater SUD reductions than tapping. Perceived disadvantages and impediments for the implementation of eEMDR were mainly of bureaucratic and technical concerns. In addition, about one third of the therapists stated that some patients were not willing to engage in eEMDR. In our study, eEMDR proved to be a practically applicable therapy method and therefore, therapists can consider using eEMDR. These findings will hopefully encourage EMDR therapists and their patients to use eEMDR due to its effectiveness and viability as an online treatment approach.